1992
DOI: 10.1029/91tc02102
|View full text |Cite
|
Sign up to set email alerts
|

Geology and geophysics of the Rukwa Rift, East Africa

Abstract: Exploration in the Rukwa rift, using gravity and seismic reflection surveys, fieldwork, and drilling has defined the structure and stratigraphy of the basin in greater detail than any other part of the Western rift. The stratigraphy comprises Precambrian basement, Karroo sandstones, shales and coals, upper Miocene red beds, and Miocene‐Recent lacustrine and fluvial sediments. During Miocene‐Recent rifting the greatest sediment input apparently came from axial fluvial systems flowing from the northwest and sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 22 publications
9
135
1
Order By: Relevance
“…These results are in good agreement with previous modeling of apatite fission track and length parameters from samples collected in the Cherangani Hills and the basement rocks SE of Lake Turkana, which revealed 60 to 70°C of cooling between approximately 60 and 50 Ma [Foster and Gleadow, 1996;Spiegel et al, 2007]. This cooling appears to have been coeval with renewed extension and tectonic subsidence in the Anza Rift [i.e., Morley et al, 1999b;Bosworth and Morley, 1994;Morley, 2002], which is inferred to have been associated with flexural upwarping of rift flanks in that region [Foster and Gleadow, 1996].…”
Section: Paleocene To Eocene (65 -50 Ma) Rapid Coolingsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are in good agreement with previous modeling of apatite fission track and length parameters from samples collected in the Cherangani Hills and the basement rocks SE of Lake Turkana, which revealed 60 to 70°C of cooling between approximately 60 and 50 Ma [Foster and Gleadow, 1996;Spiegel et al, 2007]. This cooling appears to have been coeval with renewed extension and tectonic subsidence in the Anza Rift [i.e., Morley et al, 1999b;Bosworth and Morley, 1994;Morley, 2002], which is inferred to have been associated with flexural upwarping of rift flanks in that region [Foster and Gleadow, 1996].…”
Section: Paleocene To Eocene (65 -50 Ma) Rapid Coolingsupporting
confidence: 81%
“…East of the present-day Elgeyo Escarpment, Paleogene normal faulting and coeval sedimentation along the proto-Kerio Basin had been previously inferred based on a pronounced negative Bouguer gravity anomaly, reflecting a thick sedimentary fill, thought to be incompatible with the amount of Neogene extension and tectonic basin subsidence [Morley et al, 1992;Mugisha et al, 1997]. As neither currently available geophysical, geological, nor thermo-chronological data suggest similar coeval Paleogene extension processes in the central and southern sectors of the Kenya Rift, it appears that early Cenozoic rifting in Kenya was focused in the greater Turkana region [i.e., Morley et al, 1992;Foster and Gleadow, 1992;Foster and Gleadow, 1996;Morley, 1999;Spiegel et al, 2007], the Anza Rift, where Mesozoic extensional faults were reactivated [i.e., Morley et al, 1999b;Bosworth and Morley, 1994], and regions as far south as the transition between the central and northern Kenya rifts (this study).…”
Section: Regional Implications For Rifting In East Africamentioning
confidence: 99%
“…In our earlier study (Kaeser et al 2006), we concluded that the porphyroclastic peridotite xenoliths essentially reflect pervasive deformation associated with decompression and cooling in the context of multiple rifting episodes to which the lithospheric mantle in this region was subjected (Anza Graben and Kenya rift; e.g., Winn et al 1993;Morley et al 2006). Thermobarometric data were interpreted in terms of a P-T path characterised by three successive stages ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2a-c) indicating that they are not cognate to their host lava. The occurrence of deformed cumulates from alkaline melts can be explained by the long-time magmatic activity in the region of Marsabit, starting in Mesozoic-Paleogene times (i.e., diabase intrusion associated with the development of the Anza Graben; Winn et al 1993;Morley et al 2006), until the development of the Marsabit shield volcano. The xenolith-bearing basanites and alkali basalts represent the youngest volcanic products (1.8-0.5 Ma; Brotzu et al 1984;Key et al 1987) and thus potentially sampled mafic lithologies accumulated earlier.…”
Section: Origin Of the Grt Websteritesmentioning
confidence: 99%
“…In the Anza Rift (Morley et al, 1999a), this corresponds to the end of the subsidence of the basin under a strike-slip tectonic regime characterized by a major unconformity and the last marine flooding in the area.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%